Factors Influencing Adoption of Two-Wheeler Electric Vehicles in Nepal - Neupane, Samulson; Shakya, Binju (Journal of Productive Discourse, 2024)
This study aimed to explore the factors influencing the adoption of two-wheeler electric vehicles (2WEVs) in Nepal during the 2022/23 period. As the adoption of electric vehicles (EVs) gains momentum worldwide, understanding the factors driving or hindering their adoption is critical for policymakers, manufacturers, and distributors in Nepal. The study collected data from 387 respondents through an online questionnaire. The questionnaire included several independent variables, such as financial incentives, social reinforcement, environmental concerns, charging infrastructure, and price. These variables were analyzed to determine their impact on the adoption of 2WEVs. Exploratory Factor Analysis was conducted to simplify the factor structure of the data and identify the suitability of the responses. By using correlation and multiple regression analyses, the findings of the study showed that price, financial incentives, and charging infrastructure had a significant impact on EV adoption. Environmental concern and social reinforcement did not show a significant relationship with the dependent variable. To improve the adoption of 2WEVs in Nepal, manufacturers and distributors need to improve their pricing compared to fuel-driven vehicles. It is also necessary to provide financial incentives, such as tax breaks and subsidies, to promote electric vehicle adoption. Additionally, the government needs to upgrade the charging infrastructure to provide convenience for electric vehicle users. Furthermore, as environmental concerns are not a top priority for Nepalese consumers, it is crucial to raise citizens' environmental awareness through educational campaigns and other initiatives.